Improving Colonoscopy Outcomes: Split Regimen, Low-volume Preparation and Addition of Simethicone - Elena CONSTANTIN; Simona Andreea BALOSU; Alexandru CONSTANTINESCU; Lucian NEGREANU (Modern Medicine)
In the field of colonoscopy preparation, the focus is on improving patient experience, optimizing bowel cleansing efficacy, and exploring innovative technologies. The ongoing advancements made colonoscopy preparation more tolerable, effective, and accessible for patients, ultimately improving the overall quality of the procedure. Current evidence supports low volume preparations and split dose regimen in most cases. Adding simethicone to PEG might bring some advantages in terms of better visibility and tolerability. In this mini review we present the main evidence regarding the low volume PEG/citrate/simethicone colonoscopy preparation solution.